Inhibiting miR-200a-3p Increases Sirtuin 1 and Mitigates Kidney Injury in a Tubular Cell Model of Diabetes and Hypertension-Related Renal Damage - Olga Martinez-Arroyo; Ana Flores-Chova; Marta Mendez-Debaets; Laia Garcia-Ferran; Lesley Escrivá; Maria Jose Forner; Josep Redón; Raquel Cortes; Ana Ortega (Biomolecules, 2025)
Hypertension and diabetes mellitus are key contributors to kidney damage, with the renal tubule playing a central role in the progression of kidney disease. MicroRNAs have important regulatory roles in renal injury and are among the most abundant cargos within extracellular vesicles (EVs), emerging as novel kidney disease biomarkers and therapeutic tools. Previously, we identified miR-200a-3p and its target SIRT1 as having a potential role in kidney injury. We aimed to evaluate miR-200a-3p levels in EVs from patient’s urine and delve into its function in causing tubular injury. We quantified miR-200a-3p urinary EV levels in hypertensive patients with and without diabetes (n = 69), 42 of which were with increased urinary albumin excretion (UAE). We analysed miR-200a-3p levels in EVs and cellular pellets, as well as their targets at mRNA and protein levels in renal tubule cells (RPTECs) subjected to high glucose and Angiotensin II treatments, and observed their influence on apoptosis, RPTEC markers and tubular injury markers. We conducted microRNA mimic and inhibitor transfections in treated RPTECs. Our findings revealed elevated miR-200a-3p levels in increased UAE patient urinary EVs, effectively discriminating UAE (AUC of 0.75, p = 0.003). In vitro, miR-200a-3p and renal injury markers increased, while RPTEC markers, SIRT1, and apoptosis decreased under treatments. Experiments using miR-200a-3p mimics and inhibitors revealed a significant impact on SIRT1 and decrease in tubular damage through miR-200a-3p inhibition. Increased levels of miR-200a-3p emerge as a potential disease marker, and its inhibition provides a therapeutic target aimed at reducing renal tubular damage linked to hypertension and diabetes.